EU Trade-Related Measures against Illegal Fishing Policy Diffusion and Effectiveness in Thailand and Australia - Kadfak, Alin (Routledge Focus on Environment and Sustainability, 2023)
Focusing on the experiences of Thailand and Australia, this book examines the impact of trade-restrictive measures as related to the EU's regulations to prevent Illegal, Unreported and Unregulated (IUU) fishing. It is widely accepted that IUU fishing is harmful, and should be stopped, but there are different approaches to tackling it. Acknowledging this, this book argues that major efforts to fight IUU fishing require careful analyses if the goal is to achieve optimal results and avoid unintended consequences. The book draws on the recent experiences of Thailand and Australia to offer an empirical examination of one increasingly prominent solution, trade-restrictive measures. With Thailand representing direct, active intervention by the EU and Australia a more indirect dispersion of policy narratives and discourses, the book provides a rounded view on how likely it is that different countries in different situations will adapt to the changing policy norms regarding IUU fishing. Understanding the reactions of countries who might be targeted, or otherwise be influenced by the policy, generates new knowledge that helps inform a more effective and scalable implementation of the policy on the part of the EU and a better governance preparedness on the part of non-EU fishing nations. In broader terms, this book exposes a key moment of change in the compatibility between environmental regulations and international trade. The EU IUU policy is a prime example of a policy that uses the mechanisms of international trade to account for environmental and conservation objectives. By way of the unilateral and trade-restrictive stance against IUU fishing, the EU has positioned itself as a major market and normative power, driving its sustainability norms outwards. This book sheds light on the efficacy of this policy setup based on the analysis of country perspectives, which is a key factor influencing its potential spread. This book will be of interest to students and scholars of international fisheries politics, marine conservation, environmental policy and international trade, and will also be of interest to policymakers working in these areas.